2022
DOI: 10.3390/cancers14020276
|View full text |Cite
|
Sign up to set email alerts
|

Canine Oral Melanoma Genomic and Transcriptomic Study Defines Two Molecular Subgroups with Different Therapeutical Targets

Abstract: Mucosal melanoma (MM) is a rare, aggressive clinical cancer. Despite recent advances in genetics and treatment, the prognosis of MM remains poor. Canine MM offers a relevant spontaneous and immunocompetent model to decipher the genetic bases and explore treatments for MM. We performed an integrative genomic and transcriptomic analysis of 32 canine MM samples, which identified two molecular subgroups with a different microenvironment and structural variant (SV) content. The overexpression of genes related to th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 98 publications
(184 reference statements)
0
3
0
Order By: Relevance
“…Rapid genetic tumor modeling in zebrafish has contributed to major discoveries in CM biology 10, 11, 12 , the functional role of CRKL in acral melanoma 13 , as well as the role of SPRED1 deletion in KIT inhibitor resistance in MM 5 . Studies of spontaneously occurring MM in canines have been fruitful 14 , but there remains a need to develop genetically engineered animal models to determine functional drivers of MM in patients.…”
Section: Main Textmentioning
confidence: 99%
“…Rapid genetic tumor modeling in zebrafish has contributed to major discoveries in CM biology 10, 11, 12 , the functional role of CRKL in acral melanoma 13 , as well as the role of SPRED1 deletion in KIT inhibitor resistance in MM 5 . Studies of spontaneously occurring MM in canines have been fruitful 14 , but there remains a need to develop genetically engineered animal models to determine functional drivers of MM in patients.…”
Section: Main Textmentioning
confidence: 99%
“…A recent study revealed that TRPM7 was involved in the proliferation of canine and human non-UV-induced melanomas. TRPM7 genes were suggested as candidate oncogenes for human mucosal melanoma [189] (Table 10).…”
Section: Prostate Cancermentioning
confidence: 99%
“…In recent years, some progress has been made in research on canine genomics [ 3 , 4 , 5 ] and transcriptomics analysis [ 6 ]. And the treatment of canine melanoma at the molecular level [ 7 , 8 ], immunotherapy [ 9 , 10 , 11 ], and other novel therapeutic approaches [ 12 , 13 , 14 , 15 ] have seen some progress.…”
Section: Introductionmentioning
confidence: 99%